O Brasil em Inferno Provisório, de Luiz Ruffato - Sousa, Francisco Elieudo Buriti de (2024)
In 2005, with the publication of the novel Mamma, son tanto felice, Brazilian writer Luiz Ruffato began the pentalogy titled Inferno Provisório, a project aiming to revisit five decades of Brazilian history from the worker's perspective. The other books in the series are O mundo inimigo (2005), Vista parcial da noite (2006), O livro das impossibilidades (2008), and Domingos sem Deus (2011). This work's central objective is to examine the definitive edition of Inferno Provisório published in 2016. Through the analysis of the novel and the observation of its aesthetic, social, and political dimensions, we will explore how a literary image of Brazil from 1950 to 2000 is constructed. By recreating the history of the Brazilian proletariat during this period, aspects of national life are brought to light through the voices of historically marginalized individuals. Identifying themes such as gender, race, and class inequality, the exclusionary modernization process, accelerated and inhumane urbanization, migration, and the feeling of non-belonging has helped us piece together the image of the country in the texts that make up the book. To this end, we established an intersection between literature and other fields of knowledge, utilizing concepts from various theoretical fields such as literary criticism, economics, sociology, and history. Among the consulted writers are Antonio Cândido, Walter Benjamin, Celso Furtado, Florestan Fernandes, Heleieth Saffioti, and Darcy Ribeiro. Through the comparative analysis of the texts and the dialogue with theory, we aim to contribute to studies focusing on contemporary Brazilian literature, especially those examining how fiction reveals the historical reality and experiences of socially marginalized classes.